2009
DOI: 10.1128/cvi.00018-09
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Defenses Induced by CpG Do Not Promote Vaccine-Induced Protection against Foot-and-Mouth Disease Virus in Pigs

Abstract: Emergency vaccination as part of the control strategies against foot-and-mouth disease virus (FMDV) has the potential to limit virus spread and reduce large-scale culling. To reduce the time between vaccination and the onset of immunity, immunostimulatory CpG was tested for its capacity to promote early protection against FMDV challenge in pigs. To this end, CpG 2142, an efficient inducer of alpha interferon, was injected intramuscularly. Increased transcription of Mx1, OAS, and IRF-7 was identified as a sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…In this study, the use of CPG ODN on its own with atAlHV-1 was not effective in inducing protection to clinical MCF, and this is also the case in the other studies in cattle where CpGODN was used as an adjuvant on its own [21-25] and in pigs with FMDV vaccination [28]. We have previously shown that the atAlHV-1 remains viable when mixed with Emulsigen adjuvant but no evidence of virus replication or persistence after prime and boost vaccination has ever been detected [15], and unpublished result.…”
Section: Discussionsupporting
confidence: 56%
“…In this study, the use of CPG ODN on its own with atAlHV-1 was not effective in inducing protection to clinical MCF, and this is also the case in the other studies in cattle where CpGODN was used as an adjuvant on its own [21-25] and in pigs with FMDV vaccination [28]. We have previously shown that the atAlHV-1 remains viable when mixed with Emulsigen adjuvant but no evidence of virus replication or persistence after prime and boost vaccination has ever been detected [15], and unpublished result.…”
Section: Discussionsupporting
confidence: 56%
“…TGEV (TGEV; strain Perdue 115) was propagated in PK15 cells [55]. The FMDV type O UK/ 2001 isolate was grown in (BHK21) cells as described previously [56]. All virus titers were determined on SK-6 cells, PK-15 cells or BHK21 cells (for CSFV, TGEV and FMDV, respectively) by standard endpoint dilution and were expressed as 50% tissue culture infectious doses (TCID 50 ) per ml.…”
Section: Viruses and Repliconsmentioning
confidence: 99%
“…Others have found TLR4, 5, 7 and 9 expressed by MoDCs [96,97]. In swine, an interferon response to the TLR9 agonist, CpG, was detected in plasmacytoid DCs, Langerhans cells and B cells [98]. Zhang et al [99] reported that swine TLR7 is stimulated by RNA oligonucleotides found in FMDV leading to expression of IFN␣ and Th1 cytokine induction.…”
Section: The Role Of Toll-like Receptors In Innate Responsesmentioning
confidence: 98%